Time Domain Simulation of Geomagnetically Induced Current (GIC) Flowing in 500‐kV Power Grid in Japan Including a Three‐Dimensional Ground Inhomogeneity. Issue 12 (5th December 2018) - Nakamura, S.; Ebihara, Y.; Fujita, S.; Goto, T.; Yamada, N.; Watari, S.; Omura, Y.
Abstract: We performed 3‐D time domain simulation of geomagnetically induced currents (GICs) flowing in the Japanese 500‐kV power grid. The three‐dimensional distribution of the geomagnetically induced electric field (GIE) was calculated by using the finite difference time domain method with a three‐dimensional electrical conductivity model constructed from a global relief model and a global map of sediment thickness. First, we imposed a uniform sheet current at 100‐km altitude with a sinusoidal perturbation to illuminate the influence of the structured ground conductivity on GIE and GIC. The simulation result shows that GIE exhibits localized, uneven distribution that can be attributed to charge accumulation due to the inhomogeneous conductivity below the Earth's surface. The charge accumulation becomes large when the conductivity gradient vector is parallel or antiparallel to the incident electric field. For given GIE, we calculated the GICs flowing in a simplified 500‐kV power grid network in Japan. The influence of the inhomogeneous ground conductivity on GIC appears to depend on a combination of the location of substations and the direction of the source current. Uneven distribution of the power grid system gives rise to intensification of the GICs flowing in remote areas where substations/power plants are distributed sparsely. Second, we imposed the sheet current with its intensity inferred from the ground magnetic disturbance for the magnetic storm of 27 May 2017. We compared the calculated GICs with the observed ones at substations around Tokyo and found a certain agreement when the uneven distribution of GIE is incorporated with the simulation. Key Points: Geoelectric field induced on the ground is calculated by time domain simulation with full 3‐D ground conductivity GIC in Japanese 500‐kV power grid is calculated and is found to be affected by localized geoelectric field and topology of power grid We simulate GIC for a moderate storm in May 2017, showing a certain agreement with the GIC observed at two substations in Japan